Principles of econometrics - Hoover, Courtney (Wilford Press, 2016)
Econometrics is a branch of economics that aims to analyze financial and economic data sets by using various statistical, mathematical and computational tools. The aim of this book is to present researches and case-studies by experts from various parts of the world that have transformed this discipline and aided its advancement. The topics elucidated in the text are game theory, numerical and computational modeling, applications of econometrics in industrial engineering, etc. It provides a comprehensive insight into the field of econometrics. It aims to expand the research in this field and contribute towards its progress.--Provided by Publisher.